Implementación de un sistema automatizado de control de incidencias y - Borbor, Lidia (2010)
The goal of this Project is to offer the market a new alternative of Web System for the managing and control of technical, operative and organizational problems in a company. Currently there are applications that realize these processes that do not agree with the company needs, this produce waste of time and money. Users nowadays require systems which can be a support for their decision making in order to visualize an immediate and accurate solution for the problems that occur among departments in an organization. This project shows us how System SACIR can realize the managing and automatized control of requirements solicited by each department in a company. This system was made with free code software in order to reduce the licensing cost for the clients. Key words: Automatized control of requirements, software open source, SACIR, decisions